The quest for reality Bohr and Wittgenstein - two complementary views - Stenholm, Stig. (Oxford : Oxford University Press, 2011)
In both science and philosophy, the 20th century saw a radical breakdown of certainty in the human worldview. Quantum theorist Stig Stenholm presents Bohr and Wittgenstein as central figures undertaking the necessary replacement of apparent order and certainty with an understanding based on limited concepts in constant flux.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Bohr, Niels, -- 1885-1962.; Wittgenstein, Ludwig, -- 1889-1951.; Certainty; Quantum theory; Logical positivism